Environmental Friendliness of Gillnet Based at Karangantu Archipelagic Fishing Port - Abdillah, Hafizh Aqil; Syafrie, Hendrawan; Susanto, Adi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
The declining fish populations and stocks are obstacles to improving fisheries resource utilization in Indonesia. Moreover, the increasing fishing effort using low selective fishing gear induces a high impact on the sustainability of fisheries resources. This study aims to determine the environmental friendliness level of the surface gillnet at the Karangantu Archipelagic Fishing Port. Interviews and observations were conducted in November 2023 through simple random sampling with 15 respondents of surface gillnet fisheries. The environmental friendliness level of surface gillnet analysis is based on FAO (1995) criteria. The fisheries used polyamide multifilament gillnet with 2-inch mesh size, length of 700 m, and height of 9 m. The main catches are narrow-barred Spanish mackerel, Indian mackerel, and scads. The surface gillnet average score is 28. The high score of surface gillnet was found on several criteria, including not damaging habitats, safe for biodiversity, and safe for fishermen. We conclude that the surface gillnet is environmentally friendly fishing gear.